Computational Technologies a First Course - Afanasyeva, Nadezhda M.; Borisov, Victor S.; Churbanov, Aleksandr G.; Grigoriev, Aleksander V.; Kolesov, Alexandr E.; Popov, Petr A.; Sirditov, Ivan K.; Vasilieva, Maria V.; Zakharov, Petr E.; Vabishchevich, Petr N. (Berlin/Boston : De Gruyter, 2015)
<!Doctype html public ""-//w3c//dtd html 4.0 transitional//en""> In this book we describe the basic elements of present computational technologies that use the algorithmic languages C/C++. The emphasis is on GNU compilers and libraries, FOSS for the solution of computational mathematics problems and visualization of the obtained data.Many examples illustrate the basic features of computational technologies.
6.4 Using styles6.5 Graph decoration; 7 Mathematical modeling; 7.1 Approximation of experimental data; 7.2 Predator-prey system; 7.3 Water infiltration; 7.4 Torsion of cylindrical bars; Bibliography; Index.
Print version record.
Keywords: Mathematics -- Data processing -- Textbooks; Computer algorithms -- Textbooks; COMPUTERS / Software Development & Engineering / Quality Assurance & Testing; Electronic books